Respuesta :

Answer:

18

Step-by-step explanation:

Given expression:

[tex]2 \times (6 \div 2 + 8) - 4[/tex]

Step-1: Simplify the expression in the parenthesis using PEMDAS

Expression obtained                        Operation of PEMDAS

 [tex]\implies 2 \times (6 \div 2 + 8) - 4[/tex]                                  

 [tex]\implies 2 \times (3 + 8) - 4[/tex]                                  D - Division

 [tex]\implies 2 \times (11) - 4[/tex]                                      A - Addition

 [tex]\implies2 \times 11 - 4[/tex]

Step-2: Simplify the expression obtained from step-1

Expression obtained                        Operation of PEMDAS

 [tex]\implies 2 \times 11 - 4[/tex]

 [tex]\implies 22 - 4[/tex]                                          M - Multiplication

 [tex]\implies 18[/tex]                                                  S - Subtraction